The Metaphorical Meanings of Imperative Verb in Holy Quran: Definition and Lexicon - Mohammed, Sabah H.; Suliman, Khalida O. (Humanities Journal of University of Zakho, 2016)
The reason behind writing this research, we found that some of the figuration meaning for the command verb in som rhetoric and linguistic books even in the Koran ,and this from often doesn’t show the truth but it refers to another meaning so, we wanted to know these figuration meaning that we couldn’t find most of them in the books .so, this research added more new meanings like faith and faithful and others as unbeliever we devided the research in two subjects.first one consists of request indication,the second part is about unrequest indications as threat ,sarcasm and reticule…etc. We ordered these commands according to the numbers mentioned in the Koran and some are ordered depending on the alphabetical order. So, we showed the reswarch as organized scheduals, this way makes the idea is easy for the readers and not forget that the most of us prefer it. The best supporters to our reswarch were the mothers of eaplanations like (kashaf, bahrelmuheet and the collects of Koran and others as dictionaries of the language ….etc. Then we concluded the research by a summary conclusion of the result. Finally we hope that we did our best to this research. Too much thanks to Allah.